2014
DOI: 10.1097/ccm.0000000000000547
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Performance Category at Hospital Discharge Predicts Long-Term Survival of Cardiac Arrest Survivors Receiving Targeted Temperature Management*

Abstract: Objective Despite recent advancements in post-cardiac arrest resuscitation, the optimal measurement of post-arrest outcome remains unclear. We hypothesized that cerebral performance category (CPC) score can predict the long-term outcome of post- arrest survivors who received targeted temperature management (TTM) during their post-arrest hospital care. Design Retrospective chart review. Setting Two academic medical centers from May, 2005 to December, 2012. Patients The medical records of 2,417 out-of-hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 50 publications
1
39
0
2
Order By: Relevance
“…Despite its limitations, the CPC score at hospital discharge was shown in two studies, one in all patients treated with TTM 19 and one in patients experiencing OHCA, 20 to predict long-term survival outcomes in post-arrest patients, with favorable CPC scores associated with a greater likelihood of long-term survival. 19,20 Recently, the construct validity of the CPC score was assessed with the conclusion that a CPC can be used to measure functional outcome, particularly when administered as a standardized interview.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its limitations, the CPC score at hospital discharge was shown in two studies, one in all patients treated with TTM 19 and one in patients experiencing OHCA, 20 to predict long-term survival outcomes in post-arrest patients, with favorable CPC scores associated with a greater likelihood of long-term survival. 19,20 Recently, the construct validity of the CPC score was assessed with the conclusion that a CPC can be used to measure functional outcome, particularly when administered as a standardized interview.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Recently, the construct validity of the CPC score was assessed with the conclusion that a CPC can be used to measure functional outcome, particularly when administered as a standardized interview. 7 Although 23% of raw CPC scores and 12% of dichotomized CPC were discordant in this study, they still showed substantial agreement in inter-rater reliability overall.…”
Section: Discussionmentioning
confidence: 99%
“…The important and noteworthy feature of this study is the fact that they looked exclusively at patients treated with hypothermia. This significantly highlights the importance of the research focus on hypothermia and also explains the slightly low sample size as only a fraction of post-cardiac arrest patients are treated with TTM (24.1%, 140/582 in this study) (9). Other studies correlating CPC with long-term survival after cardiac arrest included a mix of patients treated with and without TTM, introducing uncertainty regarding the validity of their results in cooled patients (10, 11).…”
mentioning
confidence: 87%
“…In this edition of Critical Care Medicine , Hsu et al adds to the growing body of literature that examines predictors of prognosis in cardiac arrest patients treated with therapeutic hypothermia (9). In their study of patients treated with targeted temperature management (TTM) of 33 to 34°C after cardiac arrest, the authors reported that good Cerebral Performance Category (CPC) scores at hospital discharge predicted longer patient survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation